Experiências de conversão em uma comunidade terapêutica religiosa feminina = Conversion experiences in a female religious therapeutic community - Targino, Janine (Ciencias sociales y religión, 2020)
This article focuses on conversion experiences in a female religious therapeutic community (CTR) located in the city of Campos dos Goytacazes, Rio de Janeiro. The research was carried out with women undergoing treatment for chemical dependence, interviewed between the years 2016 and 2018, who reported in the situations of interviews their experiences of religious conversion. Field observations and interviews were also made with CTR leaders. The data from the interviews show us that the conversion represents, within the scope of this CTR, an extremely important stage for carrying out the proposed treatment.